Uranium-niobium-rich alteration products after “pisekite”, an intimate mixture of Y,REE,Nb,Ta,Ti-oxide minerals from the Obrazek I pegmatite, Pisek, Czech Republic - Skoda,R.; Novak,M.; Cicha,J. (Journal of Geosciences, 2011)
An improperly described association, further called “pisekite” aggregate, of fine-grained, mostly metamict U, Th-enriched Y,REE,Nb,Ta,Ti-oxide minerals from Obrazek I pegmatite, Pisek, forms an intimate mixture of polycrase-(Y), samarskite-(Y) and fergusonite-(Y). It underwent a low-temperature hydrothermal alteration the products of which are depleted in Y and REE > U and significantly enriched in Si, As and P. Two distinct assemblages of secondary phases were recognized to be associated with “pisekite” aggregate, namely (i) that developed within the central parts of the aggregate and (ii) pocket assemblage in albite adjacent to it. Both assemblages are dominated by Fe-rich smectite. “Pisekite” aggregate is intensively replaced by U,Nb,Ti,Fe,As,P- rich phases of variable chemical composition: phase A (Nb > Ti > Fe > U > As) from the first assemblage, as well as phases B (U ˜ Nb >Ti > As > P > Fe) and C (U > Nb > As > Fe > Ti) from the second assemblage. Associated pharmacosiderite and kahlerite/metakahlerite as well as Fe-rich smectite indicate a low temperature of the alteration processes (less than 150-200 °C). Whereas the “pisekite” aggregate was the likely source of U, Nb and Ti, arsenopyrite of the host pegmatite yielded As with Fe. The textural features show that the Fe-rich smectite replacement by the U,Nb-rich phases A, B and C took place on a micrometer scale, and these highly heterogeneous U,Nb-rich phases likely represent a mixture of nanoscale, possibly amorphous hydrated oxides, phosphates-arsenates as well as silicates of U, Fe and Ca.
Keywords: uranium; polycrase-(Y); samarskite-(Y); fergusonite-(Y); kahlerite; smectite